Bibliotekarstwo łódzkie z lat 1945–1953 w ocenach i sprawozdaniach z tego okresu - Dróżdż, Andrzej (Acta Universitatis Lodziensis. Folia Librorum, 2014)
The main scientific objective of this article is to present the history and functioning of libraries in Lodz and the Lodz region in the years 1945-1953: development of libraries, promotion of reading, as well as documenting the course of propaganda and destruction of books incompatible with the political needs of the central government in this period. 61 W.